Thrombin generation profiles as predictors of symptomatic venous thromboembolism after trauma: A prospective cohort study. Issue 3 (September 2017) - Park, Myung S.; Spears, Grant M.; Bailey, Kent R.; Xue, Ailing; Ferrara, Michael J.; Headlee, Amy; Dhillon, Sabtir K.; Jenkins, Donald H.; Zietlow, Scott P.; Harmsen, William S.; Ashrani, Aneel A.; Heit, John A.
Abstract : BACKGROUND: Reliable biomarkers predictive of venous thromboembolism (VTE) after acute trauma are uncertain. The objective of the study was to identify risk factors for symptomatic VTE after trauma, including individual plasma coagulome characteristics as reflected by thrombin generation. METHODS: In a prospective, case-cohort study, trauma patients were enrolled over the 4.5-year period, 2011 to 2015. Blood was collected by venipuncture into 3.2% trisodium citrate at 0, 6, 12, 24, and 72 hours after injury and at hospital discharge. Platelet poor plasma was stored at −80 °C until analysis. Thrombin generation, as determined by the calibrated automated thrombogram (CAT) using 5 pM tissue factor (TF)/4 μM phospholipid (PS), was reported as peak height (nM thrombin) and time to peak height (ttPeak [minutes]). Data are presented as median [IQR] or hazard ratio with 95% CI. RESULTS: Among 453 trauma patients (injury severity score = 13.0 [6.0, 22.0], hospital length of stay = 4.0 [2.0, 10.0] days, age = 49 [28, 64] years, 71% male, 96% with blunt mechanism, mortality 3.2%), 83 developed symptomatic VTE within 92 days after injury (35 [42%] after hospital discharge). In a weighted, multivariate Cox model that included clinical and CAT characteristics available within 24 hours of admission, increased patient age (1.35 [1.19, 1.52] per 10 years, p < 0.0001), body mass index ≥30 kg/m 2 (4.45 [2.13, 9.31], p < 0.0001), any surgery requiring general anesthesia (2.53 [1.53, 4.19], p = 0.0003) and first available ttPeak (1.67 [1.29, 2.15], p < 0.00001) were independent predictors of incident symptomatic VTE within 92 days after trauma (C-statistic = 0.799). CONCLUSION: The individual's plasma coagulome (as reflected by thrombin generation) is an independent predictor of VTE after trauma. Clinical characteristics and ttPeak can be used to stratify acute trauma patients into high and low risk for VTE. LEVEL OF EVIDENCE: Prognostic, level III.